Beyond disagreement open remedies in human rights adjudication - Sathanapally, Aruna, 1981- (Oxford : Oxford University Press, 2013)
Providing an empirical analysis of declarations of incompatibility under the UK Human Rights Act and their aftermath in the legislative process, this book details these 'open remedies' and draws comparisons with similar human rights mechanisms in the US, Canada, South Africa, and Australia.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Human rights; Conflict of laws -- Administrative procedure